A phase 2 trial of avelumab in men with aggressive-variant or neuroendocrine prostate cancer - Brown, Landon C; Halabi, Susan; Somarelli, Jason A; Humeniuk, Michael; Wu, Yuan; Oyekunle, Taofik; Howard, Lauren; Huang, Jiaoti; Anand, Monika; Davies, Catrin; Patel, Prekshaben; Staats, Janet; et al. (Prostate cancer and prostatic diseases, 2022)
Men with progressive neuroendocrine or aggressive-variant metastatic prostate cancer (NEPC/AVPC) have a poor prognosis and limited treatment options, and immunotherapy has not been tested in such patients. We conducted an open label single center phase 2 trial (NCT03179410) of men with progressive NEPC/AVPC either defined by histology or AVPC criteria. Avelumab (10 mg/kg every 2 weeks) was administered until progression or unacceptable toxicity. The primary endpoint was overall response rate (ORR). Secondary endpoints included ORR, radiographic progression-free survival (rPFS), overall survival, and safety. Correlative studies included longitudinal peripheral blood immune phenotyping. The study was limited by the small number of patients enrolled and by the early termination due to COVID-19. A total of 15 men with AVPC/NEPC were enrolled. The median age was 71 (range 51-85 years), and men had received a median of two prior therapies (range 1-3). Median PSA was 54 ng/dl (range 0-393), and 73% of men had liver metastasis. The ORR with avelumab in this setting by iRECIST or RECIST 1.1 was 6.7%, including one patient (6.7%) with a complete remission (CR), 20% with stable disease, and 67% with progressive disease. The patient with the CR had an MSH2 somatic mutation and MSI-high NEPC with central nervous system metastases, and his CR remains durable off all therapy for 2 years. The median rPFS was 1.8 months (95% CI 1.6-3.6 months), and median overall survival was 7.4 months (85% CI 2.8-12.6 months). Safety was consistent with the known profile of avelumab. Phenotyping of peripheral immune subsets suggest enhanced CXCR2-dependent myeloid and T-cell responses in this extraordinary responder. While the study was terminated early due to slow enrollment at the onset of the COVID-19 pandemic and lower than anticipated objective response rate, PD-L1 inhibition with avelumab monotherapy showed poor efficacy in patients with microsatellite stable NEPC/AVPC. Immune profiling revealed enhanced CXCR2 positive immune cell activation in the one extraordinary responder, suggesting potential mechanisms for further immunotherapy development in this population.